PENGEMBANGAN KOMPETENSI ASN DI ERA NEW NORMAL: QUO VADIS WIDYAISWARA? - Ratnaningsih Hidayati (Pusat Pembinaan Jabatan Fungsional Bidang Pengembangan Kompetensi Pegawai ASN, 2021)
Distance learning by utilizing information technology has now become a necessity. This has been accelerated by the outbreak of the Covid 19 pandemic. The purpose of this study was to explore the readiness of learning facilitators in training for ASN in the face of changing the learning paradigm from traditional face-to-face to e-learning. This study used a qualitative approach. The data mining technique used was interviews with several Widyaiswaras from young, middle, and major positions. In addition, data mining is also carried out from relevant secondary sources. The results showed that not all Widyaiswara were ready to face the paradigm shift from conventional training to e-learning. Widyaiswara really needs the development of competencies related to digital literacy. The Widyaiswara Guiding Agency, namely the State Administration Institute, is expected to provide facilitation for widyaiswara and also encourage government training institutions to equip widyaiswara so that they are competent in the use of learning technology.